2013
DOI: 10.1093/cid/cit503
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Sequence Type 131 (ST131) Subclone H30 as an Emergent Multidrug-Resistant Pathogen Among US Veterans

Abstract: Among US veterans, ST131, primarily its H30 subclone, accounts for most antimicrobial-resistant E. coli and is the dominant E. coli strain overall. Possible contributors include multidrug resistance, extensive virulence gene content, and ongoing transmission. Focused attention to ST131, especially its H30 subclone, could reduce infection-related morbidity, mortality, and costs among veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
176
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(192 citation statements)
references
References 29 publications
15
176
1
Order By: Relevance
“…A comparison of the present data with the findings of Colpan et al regarding clinical E. coli isolates from 24 Veterans Affairs medical centers in 2011 (Colpan et al, 2013) showed that, here, ST131 and ST131-H30 accounted for only half as great a proportion of ESBLproducing isolates (i.e., 32% versus 64%), but a fairly similar proportion of non-ESBL-producing or total isolates (26% versus 24%). Further study would be needed to clarify the basis for these findings.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…A comparison of the present data with the findings of Colpan et al regarding clinical E. coli isolates from 24 Veterans Affairs medical centers in 2011 (Colpan et al, 2013) showed that, here, ST131 and ST131-H30 accounted for only half as great a proportion of ESBLproducing isolates (i.e., 32% versus 64%), but a fairly similar proportion of non-ESBL-producing or total isolates (26% versus 24%). Further study would be needed to clarify the basis for these findings.…”
Section: Discussionsupporting
confidence: 63%
“…A recent study determined that among E. coli clinical isolates from 24 VA medical centers across the U.S. E. coli ST131 (predominantly ST131-H30) accounted for 7% of fluoroquinolone-susceptible, 78% of fluoroquinolone-resistant, and 64% of ESBL-producing isolates, and for 28% of E. coli isolates overall (Colpan et al, 2013). Based on the 2% overall prevalence of ceftriaxone resistance (a proxy for ESBL production) in that study's source population (Colpan et al, 2013), back calculations indicated that ST131 accounted for 26% of that study's non-ESBL producing E. coli isolates.…”
Section: St131 Prevalence Comparison With 2011 Data From Usveteransmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies involving whole genome sequencing of ST131 isolates collected from multiple countries came to the same conclusion that fluoroquinolone resistance within ST131 was confined almost entirely to the H30 subclone and that CTX-M-15 producers clustered within a nested subclone, designated H30-Rx (Petty et al, 2014;Price et al, 2013 and 16.9 to 66.2 %, respectively, depending on the isolate sources and selection criteria (Banerjee et al, 2013b;Price et al, 2013). The majority of the ST131 isolates that have been tested for the H30 and H30-Rx subclones were collected from North America and Europe; relatively few isolates were from Asia (Banerjee et al, 2013a, b;Colpan et al, 2013;Johnson et al, 2013Johnson et al, , 2014Tchesnokova et al, 2013). Additionally, few studies have assessed the association of host factors with the two ST131 subclones (Banerjee & Johnson, 2014).…”
Section: Introductionmentioning
confidence: 99%